Increasing the Capacity of BUMDes Rekso Wijoyo Tambong Village through Training in Preparing and Organizing Thematic Tourism Packages for Agrotourism, Geotourism and Historical Tourism - Muhamad Ari Perdana; Ayu Wanda Febrian; Adetiya Prananda Putra; Nanda Dwi Saputra (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
This community service investigates the designation of Tambong Village as a Tourist Village by the Banyuwangi Regency Government, focusing on the development of agriculture-based tourism (agrotourism) under the initiative